Quality of life in patients undergoing orthognathic surgery – A two-centered Swedish study. Issue 8 (August 2016) - Silva, I.; Cardemil, C.; Kashani, H.; Bazargani, F.; Tarnow, P.; Rasmusson, L.; Suska, F.
Abstract: Aim: Surgical corrections of dentofacial deformities have both physical and psychological impact on quality of life (QoL). The objectives of the present study were to evaluate the impact of oral health related problems on QoL before and after a combination of orthodontic treatment and orthognathic surgery. Additionally, the study aimed to identify correlations between different dentofacial patterns and possible improvements due to treatment. Material and methods: In a prospective study, we evaluated fifty patients before start of treatment, 6 weeks and 6 months postoperatively. The questionnaires used were: OHIP-14 (Short Form Oral Health Impact Profile), a condition-specific QOL approach (Orthognathic Quality of Life Questionnaires; OQLQ) and a social-demographic questionnaire. Results: There was a statistically significant improvement in the OHIP domains from baseline to 6 months follow-up and for the OQLQ, the improvement was significant both at 6 weeks and 6 months in relation to the baseline data. Conclusion: Significant improvement of quality of life over time is proved by both OHIP-14 and OQLQ in the present study. Socio-demographic and holistic considerations are important when evaluating treatment outcome after combined orthodontic and orthognatic surgery. However, longer follow-up would be beneficial.